Fodor's 2016 Arizona & the Grand Canyon - Bitler, Teresa; Levin, Mara; Riley, Elise; Weatherford, Mike; Fodor's Travel Publications, Inc. (New York Fodor's Travel, 2016)
Detailed and timely information on accommodations, restaurants and local attractions highlight these updated travel guides, which feature all-new covers, a dramatic visual design, symbols to indicate budget options, must-see ratings, multi-day itineraries, Smart Travel Tips, helpful bulleted maps, tips on transportation, guidelines for shopping excursions and other valuable features.
Experience Arizona -- Phoenix, Scottsdale, and Tempe -- Grand Canyon National Park -- North-Central Arizona -- Northeast Arizona -- Eastern Arizona -- Tucson -- Southern Arizona -- Northwest Arizona and Southeast Nevada -- Travel smart Arizona & the Grand Canyon.
Previously published: 2015.
"Outdoor fun, southwestern eats, natural wonders"--Cover.
Includes index.
Keywords: Arizona; Grand Canyon National Park (Ariz.); Arizona -- Grand Canyon National Park; Guidebooks